European Green Deal: Using ambitious climate targets and renewable energy to climb out of the economic crisis - Karlo Hainsch; Leonard Göke; Claudia Kemfert; Pao-Yu Oei; Christian R. von Hirschhausen (DIW Weekly Report, 2020)
The European Green Deal, initiated by the EU Commission, is a package of measures aimed at decarbonization and sustainable economic development with the goal of making the European Union climate neutral by 2050. To achieve this goal, the emission reductions target must be increased from 40 percent to 65 percent compared to 1990 levels, as the model calculations in this Weekly Report show. Fossil and nuclear power plants must be completely substituted with 100 percent renewable energy sources. Compared to the current course, over 60 billion tons of CO2 could be saved as a result. Expansive investments must be made to build a solid basis for the current national and EU-level economic stimulus packages. Investments in renewable energy require around 3,000 billion euros; however, they are accompanied by savings of almost 2,000 billion euros from not importing fossil fuels. The German EU Council Presidency (its term lasting from July to December 2020) faces the challenge of persuading the Member States to adopt a common strategy for implementing the European Green Deal as part of their respective economic stimulus packages.
Keywords: Q54; L94; 330; Europe; investment; energy; climate policy; recovery